1999
DOI: 10.1021/jp9918656
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Minimum Polarizability Principle in Molecular Vibrations and Internal Rotations:  An ab Initio SCF Study

Abstract: Molecular vibrations in ammonia (NH3) and hydrogen sulfide (H2S), and internal rotations in hydrogen peroxide (HOOH), hydrogen thioperoxide (HSOH), hydrogen persulfide (HSSH), and ethylene (C2H4) are studied using ab initio SCF methods at the Hartree−Fock level using a standard Pople 6-311G** basis set. Polarizability values are calculated using both Pople's and Sadlej's basis sets. Any nontotally symmetric distortion in bond length or bond angle along the vibrational symmetry coordinates of a molecule around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 18 publications
3
105
0
Order By: Relevance
“…However, relaxation of these constraints seems to be permissible, and in particular, it has been found that in most cases the MHP still holds even though the chemical and external potentials vary during the molecular vibration, internal rotation or along the reaction coordinate. 12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Hereafter, we will refer to the generalized MHP ͑GMHP͒ or MPP ͑GMPP͒ as the maximum hardness or minimum polarizability principles that do not require the constancy of chemical and external potentials during molecular change. It is worth emphasizing that the generalized versions of these principles have not been proven.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, relaxation of these constraints seems to be permissible, and in particular, it has been found that in most cases the MHP still holds even though the chemical and external potentials vary during the molecular vibration, internal rotation or along the reaction coordinate. 12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Hereafter, we will refer to the generalized MHP ͑GMHP͒ or MPP ͑GMPP͒ as the maximum hardness or minimum polarizability principles that do not require the constancy of chemical and external potentials during molecular change. It is worth emphasizing that the generalized versions of these principles have not been proven.…”
Section: Introductionmentioning
confidence: 99%
“…11 As a consequence, the MHP and MPP are expected to be obeyed for nontotally symmetric vibrations, as confirmed by most numerical calculations of hardness and polarizability along the nontotally symmetric normal modes performed so far. 9,[15][16][17][18] For totally symmetric distorsions, the situation is drastically different. Now, starting from the equilibrium geometry the hardness keeps increasing steadily as the nuclei approach each other.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, all electronic structures down to the amino acid levels and even to individual atoms within the amino acids can be displayed. According to the principle of maximum hardness (PMH) [69,70], the HOMO-LUMO gap (ε LUMO − ε HOMO ) can be related to maximum hardness η = ½ (ε LUMO − ε HOMO ) and used to roughly estimate the stability of each molecular fragment [71,72]. Based on this simple rule, the fifth trimer (Gly-Ala-Ala) and the sixth trimer (Gly-Ala-Hyp) in the middle part of the α 2 (I) chain should be more stable than the other trimers.…”
Section: Results and Discussion On The Collagen Modelmentioning
confidence: 99%
“…63 The minima and maximum of hardness indicate the presence of two transition states and an equilibrium structure, respectively. Then, the number of the stationary points in the energy and hardness profiles is the same.…”
Section: H 2 Omentioning
confidence: 99%